Intermediate cities and automobile parks in Chile. Territorial sustainability in check? - Francisco Maturana; Mauricio Morales; Ulises Sepúlveda; Johana Maldonado (Íconos)
Urbanization is developing in all areas of the planet. This process has an impact on the mobility of people in the city and the means to move both in metropolitan areas and in medium-sized cities. This article analyzes the evolution, between 2001 and 2019, of the motorized vehicle fleet in the communes of Chile in intermediate cities. Through the compilation and systematization of databases provided by official agencies and the use of statistical analysis, the explosive but heterogeneous increase of the vehicle fleet in the communes of such cities is made visible. This differentiated increase does not follow patterns related to urban hierarchy, poverty, income, or even those communes with a successful development model sustained by raw material exports. Based on the above, it is concluded that there are other multi-causal elements in the evolution of such vehicle fleet, such as inter-urban flows between communes, the morphology of the city or climatic conditions. These results invite us to reflect on the type of city that is being built and the problems in the sustainability of such growth for urban areas in the near future, due to the absence or weakness of pertinent territorial policies that favor other means of mobility.